All optical Millimeter-wave signal generation and transmission for radio over fiber (RoF) link - Norliza Mohamed; Sevia Mahdaliza Idrus; Azura Hamzah; Suriani Mohd Sam; Norulhusna Ahmad; Hazilah Md Kaidi; Rudzidatul Akmam Dziyauddin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Fiber-based wireless system has become a promising solution as a cost- effective communication and it offers high capacity network with millimeter- wave (mm-wave) signal transmission. The system significantly offers superior possible bandwidths for both fiber and free-space applications. Hence, with the increased capacity as well as wireless mobile network applications particularly at mm-wave signal, radio over fiber (RoF) technology is the utmost option. Nevertheless, when high frequency signal transmission is involved, power fading or dispersion effect limits the performance of RoF link. Therefore, this work proposed a RoF system by integrating remote optical local oscillator (LO) with frequency up-conversion at the base station (BS). All optical mm-wave signals are generated and transmitted for the RoF link. The effects of the changes of fiber loop length, optical power of the continuous wave (CW) optical laser carrier and responsivity value of the p-i-n photodiode (PD) mainly at 40 GHz are investigated and the power fading effects are discussed.